Filozofska analiza mehanizmov kognitivnega modeliranja in umetne inteligence v izobraževanju - Aberšek, Boris; Kordigel Aberšek, Metka (University of Maribor Press, 2025)
Philosophical Analysis of Mechanisms of Cognitive Modeling and Artificial Intelligence in Education. Technology is both a cause and a consequence for an ever faster changing society. Speaking about technology today, we speak above all about intelligent systems, so called cybernetic systems, the system which contains, if we speak in technological language, engine equipment, machines and devices (the human body), and program equipment ‒ intelligence – mind (in the language of humans), also feelings, intention conditions, emotions, etc. Many problems connected with modern technologies are therefore also connected with (artificial) intelligence (AI). To solve problems connected with artificial intelligence, above all we need common knowledge about the world, society, and human beings, which is a philosophical problem. Therefore, it is very important for everyone who has to take decisions in the field of artificial intelligence to understand the basics of general mechanisms of intelligence ‒ philosophy of the mind, to understand the way natural and artificial intelligence functions especially in the area of education.